2017
DOI: 10.17219/acem/64823
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between iron content in knee joint tissues and chosen indices of peripheral blood morphology

Abstract: Background. Iron as a cofactor of enzymes takes part in the synthesis of the bone matrix. Severe deficiency of iron reduces the strength and mineral density of bones, whereas its excess may increase oxidative stress. In this context, it is essential to determine the iron content in knee joint tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The reasons for our sampling choices are as follows: (I) the femoral greater trochanter and the proximal part of the tibia have similar biomechanical characteristics and both are nonstress concentration areas (12)(13)(14)(15). According to Wolff's laws, the structure of the skeleton changes with the stress load it receives; thus, the two parts should have similar bone structures; (II) previous reports have shown that there is no significant difference in the concentrations of trace elements, including Cd, Cr, Zn, Fe, Ca, and many other metal elements, between the femur and the tibia in humans, chickens, and rabbits (16)(17)(18)(19). Therefore, we believe that the cancellous bone samples we obtained from the femur and the tibia have consistent structures and can be used for side-by-side comparisons.…”
Section: Table 5 Pearson's Correlation Analysis Between Osteopenia Anmentioning
confidence: 99%
“…The reasons for our sampling choices are as follows: (I) the femoral greater trochanter and the proximal part of the tibia have similar biomechanical characteristics and both are nonstress concentration areas (12)(13)(14)(15). According to Wolff's laws, the structure of the skeleton changes with the stress load it receives; thus, the two parts should have similar bone structures; (II) previous reports have shown that there is no significant difference in the concentrations of trace elements, including Cd, Cr, Zn, Fe, Ca, and many other metal elements, between the femur and the tibia in humans, chickens, and rabbits (16)(17)(18)(19). Therefore, we believe that the cancellous bone samples we obtained from the femur and the tibia have consistent structures and can be used for side-by-side comparisons.…”
Section: Table 5 Pearson's Correlation Analysis Between Osteopenia Anmentioning
confidence: 99%
“…Budis et al [48] found similar Fe concentrations in the cartilage and spongy bone in men and women. Brodziak-Dopierała et al [49] also noted no statistically significant differences in Fe concentration in the meniscus between men and women. Some researchers have observed differences in Fe concentration between older and younger patients; however, those differences are usually slight [46,50,51].…”
Section: Discussionmentioning
confidence: 91%
“…Evidence has shown temporal and spatial changes in iron homeostasis and lipid peroxidation. Brodziak-Dopierała et al [ 125 ] found significantly different levels of iron in various components of the knee joint in patients with OA. The highest iron content was found in the femoral bone portion of the knee joint followed by the meniscus, and the lowest iron content was found in the tibia portion.…”
Section: Discussionmentioning
confidence: 99%